Pengaruh Kinerja Lingkungan, Biaya Lingkungan Dan Risiko Bisnis Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2019-2023) - Dhea Maria Butar Butar, Wynne; Efni, Yulia; Rahmayanti, Elvi (Bahtera Inovasi, 2025)
This study aims to determine the effect of environmental performance, environmental costs and business risk on firm value. This research is a quantitative research. The population in this study included all food and beverage subsector companies. The sample in this study amounted to 24 companies. The sampling method used is purposive sampling. Hypothesis testing using multiple regression analysis. The results showed that environmental performance and business risk had no effect on firm value. Environmental costs have a positive effect on firm value.